Basic Leadership Training by Personnel of Sat Brimob Polda West Sumatera for Students of MAN 2 Padang Panjang - Suci Fajrina; Lufri Lufri; Sandi Fransisco Pratama (Fakultas MIPA Universitas Negeri Padang, 2025)
MAN 2 Padang Panjang is one of the best state Islamic high schools in West Sumatra. This school is very focused on building quality student character. However, the main problem experienced by students of MAN 2 Padang Panjang is the lack of student confidence to take on leadership roles in school activities or outside the classroom. This was expressed by the Head of MAN 2 Padang Panjang through a letter of request to the Head of LPPM UNP to carry out community service, especially in the form of Basic Leadership Training (LDK) for students of MAN 2 Padang Panjang. LDK plays an important role in shaping the character, skills, and positive attitudes needed by students to become effective leaders in the future. Therefore, LDK is important in training students' leadership skills. The Brimob Unit of the West Sumatra Police has the responsibility to build the leadership capacity of the younger generation as an effort to build a better community. As part of the police institution, the Brimob Unit has experience and expertise in the field of leadership that can be conveyed to the younger generation. The purpose of this PKM is to provide basic leadership training by the Brimob Unit Personnel of the West Sumatra Police to students of MAN 2 Padang Panjang. The long-term goal of this program is to develop skills and positive attitudes of MAN 2 Padang Panjang students to become effective leaders in the future. Participants in this PKM are 100 students of MAN 2 Padang Panjang. Personnel from the West Sumatra Police Mobile Brigade Unit act as trainers. The implementers of this PKM activity are lecturers from the Biology Department, FMIPA UNP with the title Basic Leadership Training by West Sumatra Police Mobile Brigade Unit Personnel for MAN 2 Padang Panjang Students.